2020
DOI: 10.1536/ihj.19-572
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for 6-Month Mortality in Elderly Patients with Heart Failure

Abstract: Prediction of short-term mortality in elderly patients with heart failure (HF) would be useful for clinicians when discussing HF management or palliative care. A prospective multicenter cohort study was conducted between July 2014 and July 2018. A total of 504 consecutive elderly patients (age !75 years) with HF (mean age 85 years, 50% women) were enrolled. We used a multiple logistic regression analysis with stepwise variable selection to select predictive variables and to determine weighted point scores. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
3
Order By: Relevance
“…Some studies of the usefulness of the ALBI score have reported its ability to predict prognosis and assist in decision making regarding treatment choices for patients with hepatocellular carcinoma, as it is a suitable tool for evaluation of hepatic reserve function. 5,6) On the other hand, in the area of heart disease, previous reports have shown that both albumin [7][8][9] and bilirubin 10,11) alone, are prognostic factors in patients with HF. Moreover, albumin is also a major component of nutritional indicators such as the prognostic nutritional index, geriatric nutritional risk index, and controlled nutritional status.…”
mentioning
confidence: 99%
“…Some studies of the usefulness of the ALBI score have reported its ability to predict prognosis and assist in decision making regarding treatment choices for patients with hepatocellular carcinoma, as it is a suitable tool for evaluation of hepatic reserve function. 5,6) On the other hand, in the area of heart disease, previous reports have shown that both albumin [7][8][9] and bilirubin 10,11) alone, are prognostic factors in patients with HF. Moreover, albumin is also a major component of nutritional indicators such as the prognostic nutritional index, geriatric nutritional risk index, and controlled nutritional status.…”
mentioning
confidence: 99%
“…Another advantage of the EPICTER score is the inclusion of only seven easy‐to‐obtain variables. Age, 6 , 11 , 12 , 20 , 24 , 25 , 26 renal function, 12 , 20 , 24 , 25 chronic obstructive pulmonary disease, 6 , 12 and advanced functional NYHA class 12 , 25 , 26 , 27 have shown their predictive ability in numerous studies and therefore have been included in many of the prognostic scores developed in acute patients. Cognitive impairment, although less represented in risk scales, 6 , 26 also predicts a poor prognosis in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, stepwise logistic regression performed best, and the ROC of the model reached 0.74-0.75. Sho Suzuki and others used multiple logistic regression analysis with stepwise variable selection to select mortality prediction variables and determine the weighted score to find the most important influencing factors [13].…”
Section: Introductionmentioning
confidence: 99%